E. coli Endotoxin Modulates the Expression of Sirtuin Proteins in PBMC in Humans - Storka, Angela; Führlinger, Gerhard; Seper, Martin; Wang, Lisa; Jew, Michael; Leisser, Asha; Wolzt, Michael (Mediators of Inflammation, 2013)
Background. Sirtuin (SIRT) proteins are class I histone deacetylases displaying gene regulatory functions in inflammatory, cancer, and metabolic diseases. These SIRT actions involve the nuclear factor κB and its inhibitor IκB pathway. However, the regulation of SIRT in vivo is still unclear. Material and Methods. In a human endotoxemia model, 20 healthy male subjects received an intravenous bolus of 2 ng/kg body weight Escherichia coli endotoxin (LPS). SIRT expression was investigated in peripheral blood mononuclear cells (PBMC) with qPCR and Western blot before and 3 hours, 6 hours, and 24 hours after LPS challenge. Additionally, SIRT regulation was studied in vitro in cultivated PBMC after incubation with 20 ng/mL LPS. Results. A downregulation by >40% of SIRT1 mRNA was detectable 3 hours after LPS and of SIRT3 mRNA 6 hours after LPS. SIRT3, IκBα, and IκB-β protein expressions were decreased 3 and 6 hours after LPS. SIRT2 mRNA or protein expression did not change following LPS. These findings were consistent in vitro and associated with augmented phosphorylation of IκB-β. Discussion. In this E. coli endotoxemia model, SIRT1 and SIRT3 mRNA expressions in PBMC in humans were reduced after LPS challenge. This suggests that SIRT may represent an inflammatory target protein in vivo.